Virtual Gaming Simulation: An Interview Study of Nurse Educators. (August 2020) - Verkuyl, Margaret; Atack, Lynda; Kamstra-Cooper, Krista; Mastrilli, Paula
Background. Two methods that provide high fidelity experiences outside of clinical settings are laboratory simulation and virtual simulation. Virtualgaming simulations are emerging and currently, there are no guidelines regarding the process. Objectives. The purpose of this study was to conduct interviews withnursing educators who use virtualgaming simulation in education to better understand the extent of use, the process, the challenges and benefits they experience, and their recommendations. Design. A qualitative, descriptive study, using purposive maximum variation sampling and interviews was conducted. Setting/Participant. Participants were selected fromnursing programs in different Canadian and American educational institutions who had teaching experience using virtualgaming simulations withnursing students in higher education. Methods. In-depth interviews were conducted using a semi-structured interview guide with opened-ended questions. The interviews were recorded and transcribed. Data analysis was completed using a thematic approach. Results. The final sample consisted of 17 participants, 11(65%) were from Canada and the remaining 6(35%) were from the United States. The data yielded three themes: Benefits of gaming for the student; Preparing students and educators for success and, The virtualgaming simulation process . Participants described the challenges of using virtualgaming simulation in education and made recommendations for best practice and future research. Conclusion. The results of this study can be used as guideposts for educators who embark on this new learning experience and researchers who wish to expand the body of knowledge in this emerging field.